A ruína da tradição em Walter Benjamin e a prosa poética de Charles Baudelaire - Fonseca, Sérgio Eduardo Carvalho (2010)
This study addresses the decline of tradition in western modernity as being the starting point for the pursuit of other kinds of expression that would better suit the new era. Walter Benjamin identified this scenario in The storyteller essay, which, by taking into account the overcoming of traditional experience by individual life experience, makes headway for his analysis of Charles Baudelaire s choc experience . Through this analysis, Benjamin reveals a number of facets inherent to the poet s thinking, both in Baudelaire s art critique and in his poetry production , as being proposals of what would be the ideal attitude capable of promoting a fruitful relationship between the individual and the modern city. This attitude would cause the individual to abandon his passiveness of character and would supply him with instruments to fully and wholly become part of the crowd without having to rely singly and solely on his own individual life experience. As an example of this new attitude in the work of Baudelaire, one finds Les Petits Poèmes en Prose. These poems are considered a supplementary part of Les Fleurs du Mal, and instead of singing to the end of an era however, the fifty fragments go one step further toward the insertion of poetry in the city s day-to-day, thus freeing it from former and ancient contingencies, or more precisely, from rhyme and verse